Archiwalia Włodzimierza Korsaka w zbiorach Wojewódzkiej i Miejskiej Biblioteki Publicznej im. Cypriana. Norwida w Zielonej Górze. Część druga - Lipińska, Alicja; Radziszewska, Maria (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Documents that form the legacy of Włodzimierz Korsak - a writer, artist and hunter - were acquired by the Norwid?s Library shortly after his death, in Decem- ber 1973. The collection consists of various handwritten documents originated in numerous locations over a long span of time, which provide a heterogeneous artistic and documentary value. Dr. Rećko?s work, published in 2003, covers only a part of the archival collection. One of the main objectives of Włodzimierz Korsak S Archives in the CoUections of the Cyprian Norwid Voivodeship and City Public Library in Zielona Góra, Part Two is to supplement and integrate the inventory of personal documents and works with the materials analyzed in the earlier publication of the same title, in order to present them complete.The work on Włodzimierz Korsak?s Archives focused on the analysis of materials and their proper organizing. The process of creating the descriptions was underpinned by the applicable regulations and guidelines for the descriptions of manuscripts. The principle of adopting information from documents in their ori- ginal wording was also applied. In case of necessity to supplement, clarify or correct the descriptions, the records were written in square brackets.As a result of the analytical work, the unknown and never published source material was divided into sixteen thematic folders, supplemented with a biblio- graphy, indexes and a graphically presented family tree of Włodzimierz Korsak. One of the forms of the artist?s work, not associated with him previously, turned out to be a completely innovative discovery - the so-called Silhouettes. Some of them, along with particularly interesting fragments of the Archives, are included at the end of this study.This publication is an excellent source material for work on the life and oeu- vre of Włodzimierz Korsak, addressed to researchers of literature and art, regio- nalists and naturalists. In recent years, attention devoted to this extraordinary man has been growing noticeably. This book meets these expectations.
Keywords: Wojewódzka i Miejska Biblioteka Publiczna im. Cypriana Norwida (Zielona Góra); Korsak, Włodzimierz (1886-1973); korespondencja; kolekcjonerstwo; rękopisy; zbiory biblioteczne; archiwa prywatne; myśliwi; correspondence; collecting; manuscripts; library collections; private archives; hunters